Історія дослідження представників родини Orchidaceae Juss. у флорі Закарпаття - Loya, V.V.; Gaponenko, M.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
The history of orchids study is enlightened, the data of species composition of Orchidaceae Juss. in Transcarpathian flora are presented.